PERANAN KEWANG LAUT DALAM PELAKSANAAN SASI LAUT DI DESA PASINALO KABUPATEN SERAM BAGIAN BARAT - Uktolseja, Novyta; Balik, Agustina (Jurnal Hukum Bisnis Bonum Commune, 2022)
The purpose of this study was to examine and analyze the implementation of Sasi Laut in Pasinalo Village, West Seram Regency and the Role of Kewang Laut in the Implementation of Sea Sasi in Pasinalo Village, West Seram Regency. Sasi is a tradition of the people of the land in Maluku, to maintain certain potential results. When sasi is implemented, the community is prohibited from picking certain plants on land and taking certain products from the sea for a period of time determined by the village government. In the implementation of Sasi Laut in Pasinalo Village, Taniwel District, West Seram Regency, the Kewang Laut institution has a very important function and role as the guardian and implementer of this Laut Sasi. The role of the Kewang Institution basically cannot be separated from the implementation of Sasi. The Kewang Institution has a very large function and role in various things that occur with the management and protection of the environment in land and sea areas that are in the area of ​​customary rights (petuanan) of a country. The role and function of the Kewang Laut still exists in Pasinalo Village which is a customary institution that always oversees every decision issued by Customary Institutions in the task of overseeing the management and utilization of natural resources in the village, but from the results of village regulations issued by the BPD, Village Heads and other customary institutions there are still some shortcomings in the village regulations, namely related to the absence of articles that regulate the role and function of the kewang both sea and land kewang in guarding and controlling the implementation of Sasi.